JENIS-JENIS IKAN YANG DIPERDAGANGKAN DI PASAR KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Yanti, Lisma; Purnama, Arief Anthonius; Ade, Filza Yulina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
This study aims to determine the types of fish that are traded in the market Rambah Samo District of Rokan Hulu. This study is a qualitative research method survey, done in January 2015. Diving research in 18 species of fish that can be found in the District of Rambah Samo market Rokan Hulu, namely fish species kapiek (Barbodes schwanenfeldii), Cork fish (Channa striata) , fish Local catfish (Clarias batrachus), carp (Cyprinus carpio), fish African catfish (Clarias gariepinus), tuna (Euthynnus affinis), fish Barau (Hampala macrolepidota), fish tilan (Mastacembelus erythrotaenia) baung fish (Mystus nemurus) , fish silais (Ompok hypophthalmus), tilapia (Oreochromis niloticus), carp (Pristolepis grooti) fish (Osphronemus gouramy), catfish (Pangasius pangsius) fish bag (Pristolepis grooti), lemongrass fish (Rastrerlliger kanagurta) mackerel (Rastrelliger faunghni), bada fish (Rasbora caudimaculata), fish sapek (Trichhogaster leerii).